Breakthrough infections with the SARS-CoV-2 omicron (B.1.1.529) variant in patients with immune-mediated inflammatory diseases. Issue 12 (5th September 2022) - Stalman, Eileen W; Wieske, Luuk; van Dam, Koos P J; Kummer, Laura Y; van Kempen, Zoé L E; Killestein, Joep; Volkers, Adriaan G; Tas, Sander W; Boekel, Laura; Wolbink, Gertjan J; Van der Kooi, Anneke J; Raaphorst, Joost; et al.
Abstract : Objectives: To compare the cumulative incidence and disease severity of reported SARS-CoV-2 omicron breakthrough infections between patients with immune-mediated inflammatory diseases (IMID) on immunosuppressants and controls, and to investigate determinants for breakthrough infections. Methods: Data were used from an ongoing national prospective multicentre cohort study on SARS-CoV-2 vaccination responses in patients with IMID in the Netherlands (Target-to-B! (T2B!) study). Patients wih IMID on immunosuppressants and controls (patients with IMID not on immunosuppressants and healthy controls) who completed primary immunisation were included. The observation period was between 1 January 2022 and 1 April 2022, during which the SARS-CoV-2 omicron (BA.1 and BA.2 subvariant) was dominant. A SARS-CoV-2 breakthrough infection was defined as a reported positive PCR and/or antigen test at least 14 days after primary immunisation. A multivariate logistic regression model was used to investigate determinants. Results: 1593 patients with IMID on immunosuppressants and 579 controls were included. The cumulative incidence of breakthrough infections was 472/1593 (29.6%; 95% CI 27% to 32%) in patients with IMID on immunosuppressants and 181/579 (31.3%; 95% CI 28% to 35%) in controls (p=0.42). Three (0.5%) participants had severe disease. Seroconversion after primary immunisation (relative risk, RR 0.71; 95% CI 0.52 to 0.96), additional vaccinations (RR 0.61; 95% CI 0.49 to 0.76) and a prior SARS-CoV-2 infection (RR 0.60; 95% CI 0.48 to 0.75) were associated with decreased risk of breakthrough infection. Conclusions: The cumulative incidence of reported SARS-CoV-2 omicron breakthrough infections was high, but similar between patients with IMID on immunosuppressants and controls, and disease severity was mostly mild. Additional vaccinations and prior SARS-CoV-2 infections may reduce the incidence of breakthrough infections.